EFFECT OF FINANCIAL DEVELOPMENT ON FINANCIAL INNOVATION IN NIGERIA - Oluganna, Eunice; Lawal, Tajudeen; Abdulazeez, Daniya Adeiza (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2018)
Financial sector is crucial for the development of a well-functioning market as it facilitate capitalinflows, mobilize savings for productive investment and facilitates the conduct and growth of aneconomy in the world. Despite the importance of financial sector development in Nigeria, financialinstitution operating in financial market were confronted with drastic changes where by old waysof doing business were no longer profitable and sustainable and unable to acquire fund with theirtraditional financial instruments. Against this background, the study investigated the effect offinancial sector development on financial innovation in Nigeria. The study employed secondarydata obtained from central bank of Nigeria statistical bulletin and World Bank database between2011 and 2017. The data obtained was subjected to system General Method of Analysis (GMM)estimator. The study concluded that upward trend of process innovation significantly influence thein depth of finance. The study recommends policy makers should design policies which willpromote and enhance the relationship between financial innovation and financial development inother to increase the supply and provision of financial service.